LOGISTICS OF EDUCATIONAL BUSINESS PROCESSES UNDER MARTIAL LAW: DIGITAL SOLUTIONS - PETUKHOVA, Liubov; VOROPAI, Nataliia; VOLIANIUK, Anastasiia (Mountain School of Ukrainian Carpaty, 2025)
Martial law, which has been ongoing in Ukraine since 2022, has presented higher education institutions with new challenges related to the need to ensure the continuity of the educational process, adapt to changes, and integrate digital solutions. This article is dedicated to the analysis of digital solutions applied in the logistics of educational business processes of higher education institutions in Ukraine under martial law, using the example of Kherson State University. The purpose of the study is to analyze the digital solutions for the logistics of educational business processes, their organization, adaptation, and effective functioning in higher education institutions of Ukraine under martial law. Special attention is paid to identifying key digital tools that contributed to maintaining the quality of education and supporting the academic community in crisis conditions. The article examines the specific features of the educational process in a relocated higher education institution during the full-scale war, in particular, identifies effective communication and feedback channels, as well as the role of digital platforms for the educational process in wartime. The research methodology includes the analysis of scientific sources and publications dedicated to the digital transformation of education, a historical review of the experience of Kherson State University in the period 2022-2024, monitoring of digital platforms and their impact on the organization of the educational process, analysis of adaptation strategies of higher education institutions in crisis conditions, and the study of the impact of digital technologies on the quality of education and the mental health of higher education students. The results of the study show that under of martial law, digital solutions have become a key factor in ensuring the continuity and quality of the educational process. Kherson State University has successfully adapted to the new challenges, using distance learning platforms, video conferences, electronic journals, and other digital tools. Effective communication and feedback channels, as well as psychological support for participants in the educational process, have played an important role. The article shows that the digitalization of educational business processes in wartime not only provides technical support but also contributes to the creation of a resilient and adaptive educational environment. The experience of Kherson State University can be useful for other higher education institutions facing similar challenges.